Phenomenology as methodological frame for intercultural learning: a focus on jazz students in Malaysia - Chan, Cheong Jan; Wong, Siao Ern (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
It is important to grasp what transpire in the learners’ mind, in responding to a foreign material of which they are tasked to embrace, internalize and apply all within the short time frame in an institutionalized setting. In this paper, I propose the use of phenomenology, combined with ethnography, as a methodological approach to foster pedagogy of empathy in mastering (inter-) cultural skills. I begin with Søren Kierkegaard’s notion on subjectivity that any things perceived within an individual is influenced or determined by one’s particularity of his/her background, and that the perception of an object also cultivates an understanding of self. From this I lay the three parts of my methodological frame of phenomenology, which is Object (which is the subject of study, that is jazz), Perception (the way the object is being grasped by the learner), and Self-image (the understanding of self, the evaluative aspect). It is hoped that through the proposed methodological frame, these different ways of understanding of the same object by the students can be revealed, and that self-efficacy, resulted from the perceived gap between the learners’ understanding of the object and their actual ability in realizing those understanding, could be examined in depth.